A scoping review of librarian involvement in competency-based medical education - John W. Cyrus; Laura Zeigen; Molly Knapp; Amy Blevins; Brandon Patterson (Journal of the Medical Library Association)
Objective: A scoping review was undertaken to understand the extent of literature on librarian involvement in competency-based medical education (CBME).